2021
DOI: 10.1111/pce.14216
|View full text |Cite
|
Sign up to set email alerts
|

(+)‐Catechin, epicatechin and epigallocatechin gallate are important inducible defensive compounds against Ectropis grisescens in tea plants

Abstract: The tea plant, Camellia sinensis (L.) O. Kuntze, is an economically important, perennial woody plant rich in catechins. Although catechins have been reported to play an important role in plant defences against microbes, their roles in the defence of tea plants against herbivores remain unknown. In this study, we allowed the larvae of Ectropis grisescens, a leaf‐feeding pest, to feed on the plants, and alternatively, we wounded the plants and then treated them with E. grisescens oral secretions (WOS). Both appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…In the current study, astragalin and EGC exhibited an antifeeding effect on E. grisescens caterpillars ( Fig. 5 ), while EC significantly inhibited the growth rate of E. grisescens caterpillars according to our study [ 34 ]. Further research revealed that JA treatment induced the accumulation of EC and EGC in tea plants ( Fig.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the current study, astragalin and EGC exhibited an antifeeding effect on E. grisescens caterpillars ( Fig. 5 ), while EC significantly inhibited the growth rate of E. grisescens caterpillars according to our study [ 34 ]. Further research revealed that JA treatment induced the accumulation of EC and EGC in tea plants ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…However, the raw material required to produce COR-MO is expensive, and the oximido is unstable under acidic conditions, which hinders the application of this antagonist in agricultural production. ZINC27640214 and ZINC43772052 were obtained through the virtual screening of 767 analogues of JA from the ZINC database based on the high-quality structural model of COI1 [ 34 ]. But the structure of COI1 used to identify these two compounds was not a crystal structure, and the function of JAZ was ignored.…”
Section: Discussionmentioning
confidence: 99%
“…67 An artificial diet supplemented with (+)-catechin, epicatechin, or epigallocatechin reduced the larval growth rates of Ectropis grisescens, indicating that these three catechins are important inducible defensive compounds against E. grisescens in tea plants. 68 However, the DAMs induced by S. mosellana larval feeding in the susceptible 6218 variety were mainly carboxylic acids and their derivatives. Furthermore, KEGG enrichment of the DAMs confirmed that the most enriched pathway in LX99 was flavonoid biosynthesis, which further shows that flavonoids are key defensive substances in wheat following infestation by S. mosellana larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Our group also found that astragalin negatively affected the growth rate of tea geometrid, and the anti-feeding effect was intensified by feeding time ( Lin et al, 2022 , accepted). JA was involved in the induction of EGCG, and there was a negative correlation between the level of EGCG in the diet and tea geometrid larval mass ( Li et al, 2021 ). In this study, significant induction of flavonoid compounds by GA treatment was noticed, especially naringenin, astragalin, and EGCG.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical insecticides are commonly used for controlling tea geometrid, but they are harmful to both the environment and human health ( Xin et al, 2016 ). Although the chemical ecology investigations of the tea plant lag far behind rice, maize, and other herbaceous plants, the current development still revealed that JA, ET, auxin, and other signaling pathways were involved in induced defense response in tea plants against tea geometrid ( Wang et al, 2015 , 2016 ; Xin et al, 2017 ; Zhang J. et al, 2020 ; Zhang X. et al, 2020 ; Li et al, 2021 ). Therefore, exploiting chemical elicitors, especially natural molecules, is an efficient and feasible strategy to increase the defense resistance of tea plants to herbivores.…”
Section: Introductionmentioning
confidence: 99%